Just Hibernate a lightweight introduction to the Hibernate framework - Konda, Madhusudhan (O'Reilly Media, 2014)
Through clear real-world examples, you'll learn Hibernate and object-relational mapping from the ground up, starting with the basics. Then you'll dive into the framework's moving parts to understand how they work in action. This book, like others in the Just series, delivers a concise, example-driven tutorial for Java beginners. You'll gain enough knowledge and confidence to start working on real-world projects with Hibernate.